Isolation of Antimicrobial Compounds From Cnestis ferruginea Vahl ex. DC (Connaraceae) Leaves Through Bioassay-Guided Fractionation - Kouakou, Koffi; Panda, Sujogya Kumar; Yang, Ming-Rong; Lu, Jing-Guang; Jiang, Zhi-Hong; Van Puyvelde, Luc; Luyten, Walter (Frontiers in Microbiology, 2019)
Different parts of Cnestis ferruginea are used in traditional African medicine for treating infectious diseases such as dysentery, bronchitis, eye troubles, conjunctivitis, sinusitis, gonorrhoea, and syphilis. Despite its long traditional use in the treatment of infections, this plant is not well studied for its in vitro antimicrobial properties. Therefore, the present study aims to establish the antimicrobial activity profile of extracts from this plant, as well as to isolate and evaluate the antimicrobial activity of the most abundant bioactive compound in C. ferruginea leaves through bioassay-guided purification, using Staphylococcus aureus as a target organism. Although both methanol and water extracts of the plant leaves proved active against S. aureus, water extracts were pursued, and subjected further to liquid-liquid partitioning (ethyl acetate, butanol and water). The ethyl acetate fraction was found to be the most potent and was subjected to silica gel chromatography. In total, 250 fractions were obtained, and those with similar TLC profiles were clustered into 22 major groups, of which pooled fraction-F6 (83 mg) was the most potent. Additional purification by HPLC resulted in two active peaks, which were identified, using a combination of NMR and mass spectrometry, as hydroquinone and caffeic acid methyl ester. Their antimicrobial activity was confirmed using a microdilution protocol on S. aureus, where hydroquinone had a stronger activity (MIC50 = 63 µg/mL) compared to caffeic acid methyl ester (>200 µg/mL). Traditionally this plant is used as an aqueous preparation to treat many infections, and the present study also demonstrated antimicrobial activity in the aqueous extract, which appears due mainly to two major water-soluble compounds isolated through bioassay-guided purification. This supports the clinical use of the aqueous extract of C. ferruginea leaves as a phytotherapeutic for bacterial infections.